Outcomes Of Adolescent Pregnancy at Kathmandu University Hospital, Dhulikhel, Kavre - Pun, K D; Chauhan, M (Kathmandu University Medical Journal, 2012)
Background Adolescence Pregnancy is a social problem worldwide with serious implication of maternal and child health. This study purposed to compare the maternal and neonatal outcome of the teenage mothers (15- 19 years) with that of the young mothers (20-24 years) to determine if adolescent pregnancies have increased risk of adverse outcomes. Objectives This st udy aims to find out the outcomes of adolescent pregnancy at Kathmandu Univeristy Hospital, Dhulikhel Hospital, KAvre. Methods Descriptive cross sectional study was done. The study included all primiparous mothers of age 15-19 (n=168) and 20-24 (n=401) recorded in the delivery record book of Dhulikhel Hospital from June 2007 to May 2008. Chi-square test and relative risk (RR) for subgroups of study population was examined using the SPSS version 10.0. Results The low birth weight baby among teenage mothers and young mothers were 28% and 26.7% respectively (p=0.572). The Relative risk of low birth weight among adolescent is 1.1 (0.75-1.684) times to that of young mothers at 95% confidence interval. Preterm birth was not associated with adolescence pregnancy (7% Vs. 11.5%, p=0.141). Normal delivery was the common mode of delivery among both groups (77.4% Vs. 74.6%). Among the neonatal complication, newborns of adolescents had greater neonatal complications than newborns of the young mothers (17.2% Vs 16.7%). Maternal complication like antepartum hemorrhage (2.4% Vs. 1.7%) and postpartum hemorrhage (0.6% Vs. 0.2%) was higher among adolescents. Conclusions Low birth weight, common neonatal complication, antepartum hemorrhage and postpartum hemorrhage are found more in adolescent group, however statistically insignificant. http://dx.doi.org/10.3126/kumj.v9i1.6263 Kathmandu Univ Med J 2011;9(1):50-3